1 The Compiled Laws of Utah: The Declaration of Independence and Constitution of the United States and Statutes of the United States Locally Applicable and Important, at 797, Toy Pistols. § 2266 (1888) - (:unkn) unknown (General Publisher, 1884)
Any one selling or giving a toy pistol to any person in this Territory, shall be guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES